Characterization of Athabasca lean oil sands and mixed surficial materials: Comparison of capillary electrophoresis/low‐resolution mass spectrometry and high‐resolution mass spectrometry. (14th April 2018) - MacLennan, Matthew S.; Peru, Kerry M.; Swyngedouw, Chris; Fleming, Ian; Chen, David D.Y.; Headley, John V.
Abstract : Rationale: Oil sands mining in Alberta, Canada, requires removal and stockpiling of considerable volumes of near‐surface overburden material. This overburden includes lean oil sands (LOS) which cannot be processed economically but contain sparingly soluble petroleum hydrocarbons and naphthenic acids, which can leach into environmental waters. In order to measure and track the leaching of dissolved constituents and distinguish industrially derived organics from naturally occurring organics in local waters, practical methods were developed for characterizing multiple sources of contaminated water leakage. Methods: Capillary electrophoresis/positive‐ion electrospray ionization low‐resolution time‐of‐flight mass spectrometry (CE/LRMS), high‐resolution negative‐ion electrospray ionization Orbitrap mass spectrometry (HRMS) and conventional gas chromatography/flame ionization detection (GC/FID) were used to characterize porewater samples collected from within Athabasca LOS and mixed surficial materials. GC/FID was used to measure total petroleum hydrocarbon and HRMS was used to measure total naphthenic acid fraction components (NAFCs). HRMS and CE/LRMS were used to characterize samples according to source. Results: The amounts of total petroleum hydrocarbon in each sample as measured by GC/FID ranged from 0.1 to 15.1 mg/L while the amounts of NAFCs as measured by HRMS ranged from 5.3 to 82.3 mg/L. Factors analysis (FA) on HRMS data visually demonstrated clustering according to sample source and was correlated to molecular formula. LRMS coupled to capillary electrophoresis separation (CE/LRMS) provides important information on NAFC isomers by adding analyte migration time data to m/z and peak intensity. Conclusions: Differences in measured amounts of total petroleum hydrocarbons by GC/FID and NAFCs by HRMS indicate that the two methods provide complementary information about the nature of dissolved organic species in a soil or water leachate samples. NAFC molecule class Ox Sy is a possible tracer for LOS seepage. CE/LRMS provides complementary information and is a feasible and practical option for source evaluation of NAFCs in water.